PENGARUH GAYA KEPEMIMPINAN TERHADAP MOTIVASI KERJA KARYAWAN DIVISI FINANCE, ACCOUNTING, TAX (FAT) PT MAKMUR RAHARJA JAKARTA - Ikhsan Thoha; Danang D Susilo (JURNAL MITRA MANAJEMEN, 2021)
AbstractLeadership style is a factor that influences employee work motivation, with a good leadership style the level of employee work motivation will increase. Giving motivation is the most important thing in one's leadership, a good leader will always provide encouragement that motivates employees to increase employee motivation.This study aims to determine the effect of leadership style on employee motivation at PT Bersama Makmur Raharja. This study used a population of 28 employees with a sample of 26 respondents, data collection techniques using a questionnaire. Data analysis techniques used are product moment correlation coefficient test, determination coefficient test and regression equation test with SPSS v20 data processing. Based on the calculation of the correlation coefficient, a value of 0.656 shows that the level of a strong relationship between leadership style and motivation, the coefficient of determination shows a value of 43%, indicating that the influence of leadership style on motivation is 43% and the remaining 57% is influenced by other factors that require research. Furthermore. Based on SPSS, the regression value of constant (a) is 64.357, while the value of leadership style (b) is 0.174, so the regression equation can be written as Y = 64.357 + 0.174X, a constant of 64.357 states that if the leadership style is 0, then the motivation level is 64.357. While the X regression coefficient of 0.174 states that each additional value of leadership style is 1, the motivation value will increase by 0.174. Based on the hypothesis test, the t value is 2.181> 2.055, where the t value> from the t table, then Ho is rejected and Ha is accepted, that is, there is an influence of leadership style on employee motivation. Keywords: Leadership Style, Motivation